2018
DOI: 10.1111/bph.14443
|View full text |Cite
|
Sign up to set email alerts
|

Clarification of the basis for the selection of requirements for publication in the British Journal of Pharmacology

Abstract: In 2015 and 2018, the British Journal of Pharmacology (BJP) published guidelines on experimental design and analysis (Curtis et al., 2015. The intention was to improve the credibility of papers published in BJP by the simplest means possible. It is all very well for a journal to elaborate a framework of best practice, with lengthy explanations for each issue considered, but if authors, reviewers and editors fail to adopt the framework because it is too complex or nuanced, then we fail as a journal. Consequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…The data and statistical analysis comply with the recommendations of the British Journal of Pharmacology on experimental design and analysis in pharmacology (Curtis, Ashton, Moon, & Ahluwalia, ) and were performed using GraphPad () or SPSS (), in agreement with BJP guidelines. All studies were designed to generate groups of equal size, and experimental animals or groups (behavioural analysis) were randomly assigned to treatment groups before being analysed blind to the experimental group.…”
Section: Methodsmentioning
confidence: 99%
“…The data and statistical analysis comply with the recommendations of the British Journal of Pharmacology on experimental design and analysis in pharmacology (Curtis, Ashton, Moon, & Ahluwalia, ) and were performed using GraphPad () or SPSS (), in agreement with BJP guidelines. All studies were designed to generate groups of equal size, and experimental animals or groups (behavioural analysis) were randomly assigned to treatment groups before being analysed blind to the experimental group.…”
Section: Methodsmentioning
confidence: 99%
“…In order to continue to build upon this success and to further enhance the impact of the journal for its readers and authors we announce the implementation of new Author Guidelines . The new PR&P Author Guidelines are aligned with recently revised author guidelines for the other ASPET and BPS journals 1‐3 and support the author‐elected manuscript referral and transfer process at PR&P . Importantly, the new Author Guidelines will be translated into Japanese, Korean, Mandarin, Portuguese, and Spanish to better assist scientists globally.…”
mentioning
confidence: 92%
“…The new guidelines also provide proscriptive instructions regarding the inclusion of methodological details, statistical analyses, and graphical data presentations. Authors should appreciate that there has been much debate regarding experimental design, statistical analysis and the reporting of research outcomes in recent years 1‐8 . There are several informative commentaries on these aspects of pharmacological research which we encourage authors to carefully read 1,3,5,6 .…”
mentioning
confidence: 99%
“…• Manipulation of EPAC1/PKC/ENT1 activity may provide additional therapeutic targets to reduce cholinergic bladder overactivity. reporting are in accordance to Curtis, Ashton, Moon, and Ahluwalia (2018). Animal studies are reported in compliance with the ARRIVE guidelines (Kilkenny, Browne, Cuthill, Emerson, & Altman, 2010)…”
Section: Introductionmentioning
confidence: 99%